Structural and Functional Changes in Mild Cognitive Impairment in Parkinson’s Disease - Halil Güllüoğlu; Duygu Hünerli; Raif Çakmur; Berril Dönmez Çolakoğlu; Emel Ada; Görsev Yener (Medicina, 2023)
Background and Objectives: The pathophysiology of mild cognitive impairment in Parkinson’s disease (PD-MCI) is still not fully elucidated. It has been shown in a few studies in the literature that volume loss in the occipital, parietal and frontal cortices and atrophy in the hippocampus of PD-MCI patients can occur in the early stages of PD. The aim of this study was to evaluate the relationship between gray and white matter volumes and different neuropsychological tests and volumetric magnetic resonance imaging parameters in patients with mild cognitive impairment in Parkinson’s disease (PD-MCI). Materials and Methods: Twenty-six PD-MCI and twenty-six healthy elderly (HC) were included in this study. Results: We found that Mini Mental State Examination, Trail Making Test Part A, Clock Drawing Test, Benton Line Judgment Orientation Test and pentagon figure-copying scores were impaired in PD-MCI patients due to the decrease in brain volumes. Conclusions: Our study revealed that among PD-MCI patients, there was a more noticeable decline in White matter volume (WMV) based on volumetric Magnetic Resonance Imaging (MRI) compared to the localized loss of GMV. We think that these abnormal neuropsychological tests in PD-MCI patients can be used as pretests in the evaluation of the stage of transition to dementia.